Aberrant expression of junctional adhesion molecule‐A contributes to the malignancy of cervical adenocarcinoma by interaction with poliovirus receptor/CD155. Issue 2 (5th December 2020) - Murakami, Taro; Takasawa, Akira; Takasawa, Kumi; Akimoto, Taishi; Aoyama, Tomoyuki; Magara, Kazufumi; Saito, Yuki; Ota, Misaki; Kyuno, Daisuke; Yamamoto, Soh; Hasegawa, Tadashi; Saito, Tsuyoshi; et al.
Abstract: Recent studies have shown that aberrant expression of tight junction proteins (TJP) contributes to malignant potential of various cancers. In the present study, we investigated the expression of junctional adhesion molecule‐A (JAM‐A), one of the transmembrane TJP, in uterine cervical adenocarcinoma and the significance of its expression for malignancy. Immunohistochemistry on human surgical specimens showed that JAM‐A was aberrantly expressed in neoplastic regions including adenocarcinoma in situ (AIS). Knockout of JAM‐A significantly suppressed cell proliferation and colony‐forming and migration abilities. We also showed that an antibody specific to an extracellular region of JAM‐A reduced cell proliferation ability and that loss of JAM‐A increased drug sensitivity of cervical adenocarcinoma cells. Based on a comprehensive proteome analysis, we found that poliovirus receptor (PVR/CD155) was regulated by JAM‐A and formed a physical interaction with JAM‐A. In human surgical specimens, PVR/CD155 expression was significantly correlated with some clinicopathological features and prognosis of cervical adenocarcinoma. Interestingly, most of the PVR/CD155‐positive cases expressed a high level of JAM‐A, and patients with the expression pattern of PVR/CD155 positive/JAM‐A high had significantly shorter periods of relapse‐free survival ( P  = .00964) and overall survival ( P  = .0204) than those for the other patients. Our observations suggest that aberrant expression of JAM‐A promotes malignancy of uterine cervical adenocarcinoma by regulation of PVR/CD155, and JAM‐A is therefore a potential therapeutic target for this malignancy. Abstract : Aberrant expression of junctional adhesion molecule‐A (JAM‐A), one of the transmembrane tight junction proteins, contributes to the malignant potential of uterine cervical adenocarcinoma. We also show that loss of JAM‐A attenuated drug resistance of cervical adenocarcinoma cells and that an anti‐JAM‐A antibody inhibited cell proliferation, indicating that JAM‐A is a potential therapeutic target of the malignancy. Moreover, we show that a novel interaction between JAM‐A and poliovirus receptor (PVR/CD155) is associated with worse prognosis of cervical adenocarcinoma.